DEVELOPMENT INTEGRATIVE MODEL FOR ACADEMIC INFORMATION SYSTEMS USING UTAUT, DELONE&MCLEAN, AND TTF - Asep Hilmi Mutakin; Asep Suhana; Permatasari, R. Willa; Arief Budiman Krama; Andrew Ghea Mahardika (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: The Academic Information System (SIAKAD) plays an important role in supporting the management of academic administration in higher education institutions, particularly for students. ABC University has implemented SIAKAD since 2018 to facilitate administrative ativities in line with its motto of a high technology campus. This study aims to measure the sucess of SIAKAD usage from the aspects of acceptance, satisfaction, suitability, and perceived benefits. The integration of the Unified Theory of Acceptance and Use of Technology (UTAUT), DeLone & McLean, and Task Technology Fit (TTF) models was carried out to obain a more comprehensive overview in assessing the success of SIAKAD. UTAUT explains the factors influencing the intention to use, DeLone & McLean emphasizes the relationship between system quality and both user satisfaction and net benefits, while TTF evaluates the fit between technology and user tasks. By combining these three models, the study addresses the limitations of each model and produces a more holistic approach in measuring acceptance, success, and the appropriateness of system use. The testing was conducted using SPSS and Structural Equation Modeling (SEM) analysis through AMOS. Keywords: siakad; utaut; delone&mclean; penerimaan teknologi; sem